Heteroresistance Is Associated With in vitro Regrowth During Colistin Treatment in Carbapenem-Resistant Klebsiella pneumoniae - Wang, Yifan; Ma, Xinqian; Zhao, Lili; He, Yukun; Yu, Wenyi; Fu, Shining; Ni, Wentao; Gao, Zhancheng (Frontiers in Microbiology, 2022)
Polymyxins including polymyxin B and colistin (polymyxin E) are considered the last resort for treating infections caused by carbapenem-resistant gram-negative bacteria. However, in vitro regrowth with the emergence of resistance during treatment is common. Polymyxin heteroresistance, particularly in Acinetobacter baumannii and Klebsiella pneumoniae, has been widely reported. This study was primarily performed to evaluate the prevalence of colistin heteroresistance in carbapenem-resistant K. pneumoniae (CR-KP) and the association between in vitro regrowth and heteroresistance. The mechanisms of colistin resistance and ability of combination therapies to suppress resistance selection were further investigated. A population analysis profile (PAP) analysis showed that 69 (71.9%) of 96 CR-KP strains had colistin heteroresistance. Time-kill assays revealed that colistin monotherapy could quickly eliminated bacterial strains without heteroresistance within the first 6 h, Conversely, it could initially reduce the number of heteroresistant strains, but then regrowth occurred rapidly. Resistance screening at 12h and 24h in the time-kill assays indicated that susceptible populations were killed, and regrowth was the exact result of the continued growth of resistant subpopulations. Colistin resistance in the regrowth subpopulations was mainly due to the overexpression of phoPQ and pmrD. Colistin combined with tetracyclines (tigecycline or minocycline) or aminoglycosides (amikacin or gentamicin) could effectively suppress resistance selection and significantly elicit in vitro synergistic effects. These findings suggested that combination therapy can be used to treat infections caused by CR-KP with colistin heteroresistance. Nevertheless, further in vivo studies considering drugs pharmacokinetics/pharmacodynamics are needed to confirm these findings.